Genomic Characterization of Vibrio spp. in Asian Seabass (Lates calcarifer, Bloch, 1790) Following Field Vaccination Using a Feed-Based Inactivated Vaccine against Vibriosis - Tahir, Nur Diyana Mohamad; Yap, Sing Yee; Nor, Norhariani Mohd.; Yasin, Ina-Salwany Md.; Azmai, Mohammad Noor Amal; Zahli, Nurul Izzati Uda; Gan, Han Ming (Universitas Airlangga, 2025)
Vibriosis outbreaks pose a significant threat to the productivity of Asian seabass culture, causing substantial losses. Nevertheless, the excessive utilization of antimicrobials exacerbates the issue by fostering the development of antimicrobial resistance (AMR). Consequently, exploring alternative disease management strategies, such as the introduction of oral vaccines into Asian seabass culture, has become a subject of ongoing investigation. This study aims to compare the genomic characteristics of different Vibrio species isolated from both orally vaccinated and unvaccinated Asian seabass populations. Archived samples of vaccinated and unvaccinated Asian seabass from one site in Selangor, Malaysia, were utilized in this sample. Briefly, the vaccinated group was administered the feed-based vaccine on week 0 (prime vaccination), 2 (booster), and 6 (second booster) at 4% body weight. At the same time, the non-vaccinated fish were fed with a commercially formulated pellet without the vaccine. Vibrio isolates identified from the gut samples were used in this study. The samples were stored at -80°C before being subjected to genomic DNA extraction, PCR, gel electrophoresis, and sequencing using Illumina and Nanopore platforms. Universal 16s primer and pyrH primer were used to identify Vibrio species. Bioinformatic analysis was done using NCBI BLAST, QUAST, BUSCO 5, CGE, and J Species. The isolates of Vibrio species exhibited smooth, convex, round, and entire colonies on TCBS agar plates, which were yellow and green. Twenty-two isolates were sent for 16s rRNA sequencing and revealed Vibrio alginolyticus (54.54%), followed by V. diabolicus (13.63%) and V. parahaemolyticus and V. harveyi (9.09% respectively). Of the 22 samples, 7 were selected for further Illumina sequencing. The whole genome sequences of the six Vibrio species isolated exhibited good coverage percentage, N50 value, Average Nucleotide Identity (ANIb), single-copy percentage, and GC content, while one sample showed low single-copy percentage and high duplicated percentage, which suggested contamination during DNA extraction. Eight novel alleles were discovered, three from the vaccinated group and five from the unvaccinated group, including the Rec, atpA, gyrB, and pyrH. A virulence factor database analysis search revealed 58 virulent genes from the unvaccinated samples and 39 virulent genes from the vaccinated samples. Overall, this research provides valuable insights into the genomic characteristics between orally vaccinated and unvaccinated cultured Asian seabass in the locality.